2019
DOI: 10.1310/sci2504-322
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Dysphagia in Individuals With Cervical Spinal Cord Injury: A Prospective Observational Cohort Study

Abstract: Objectives: To identify and describe the types and time course of dysphagia following cervical spinal cord injury (SCI). Methods: This was a prospective cohort study conducted in an SCI inpatient rehabilitation unit. Seventy-six individuals with SCI were enrolled. Inclusion criteria were age 18 years or older, admitted into SCI inpatient rehabilitation unit, and medically stable for participation in bedside swallow evaluation (BSE) and videofluoroscopic swallow study (VFSS). All participants first underwent a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Regarding the relation between CSCI and swallowing function, previous studies have shown that older age is a signi cant risk factor for dysphagia [1,3,4,5,19]. Our results show the same tendency.…”
Section: Association Between Age and Oral Intake At Dischargesupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the relation between CSCI and swallowing function, previous studies have shown that older age is a signi cant risk factor for dysphagia [1,3,4,5,19]. Our results show the same tendency.…”
Section: Association Between Age and Oral Intake At Dischargesupporting
confidence: 86%
“…Dysphagia is a common secondary complication of cervical spinal-cord injury (CSCI) with an estimated incidence of 22.5-41.0% [1][2][3][4]. A recent scoping review claimed that untreated dysphagia in patients with CSCI may lead to an increase in the length of hospital stay and overall cost of care, and a decrease in patients' quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation means ventilation through a tracheostomy or an endotracheal tube [ 29 ]. Dysphagia is commonly diagnosed by a swallow evaluation at the bedside, a flexible fiberoptic endoscopy evaluation of swallowing, or a videofluoroscopic swallow study [ 30 ]. Dummy variables were created, and the category with the hypothesized lowest incidence was chosen as the reference category.…”
Section: Methodsmentioning
confidence: 99%
“…Dysphagia is a common secondary complication that often accompanies cervical spinal cord injury (CSCI). The incidence of dysphagia in individuals with CSCI ranges from 20%-40% [1][2][3][4]. Dysphagia requires attention because it can cause fatal respiratory diseases such as aspiration pneumonia, one of the leading cause of death among individuals with CSCI [5].…”
Section: Introductionmentioning
confidence: 99%